The Economic Foundations of the Rule of Law in the Russian Federation - Kuksin, Ivan N.; Allalyev, Ruslan M.; Lipunov, Valery I.; Tyurin, Ilya V. (International Journal of Criminology and Sociology, 2022)
This study, based on the economic and legal metrics of the Russian Federation, considers the possibility of implementing the concept of the rule of law in the modern world. The study emphasises the issue of the rule of law in any country being directly related to the problem of redistribution of public goods. In many ways, this can be considered an example of how economic stability ensures legal stability. The research methodology includes a dialectical method, which allowed to ensure compliance with the principles of scientific knowledge. The study shows the dynamics of ensuring human rights, the distribution of income and expenses in society over different periods in the history of the Russian Federation. In this regard, the authors come to the conclusion that the perception and functions of the concept of the rule of law will soon deviate from classical liberal values towards the basic ideas of social equality and justice.